Assessing multifunctionality and climate smartness of landscapes in Ethiopia - Tamene, Lulseged D.; Abera, Wuletawu; Mulatu, Kalkidan Ayele; Ayalew, Workneh (2021)
Integrated implementation of various land management options is the key for successful land restoration programs. Integrated sustainable land management (SLM) practices could improve land restoration success and enhance multiple ecosystem services generated by the landscape. Implementation of land and water management options at landscape level can cause tradeoffs due to conflicting land uses and varying needs of land users. It is thus essential to assess the climate-smartness of those landscapes to sustain the benefits associated with the management practices. We used various in-situ data, empirical and the Integrated Valuation of Ecosystem Services and Trade-offs (INVEST) models to assess the multifunctionality of landscapes and evaluate the associated benefits enjoyed in selected landscapes of Ethiopia. We employed a climate smartness landscape index to determine the climate-smartness of those landscapes by integrating multifunctional services provided by the landscapes due to the various interventions. We obtained a positive change in multiple ecosystem services due to land restoration efforts in four watersheds in Ethiopia. The result is substantiated by both modelling results and in-situ observation data. Even though the land management activities conducted in the study watersheds brought a positive impact, the optimal scenario shows that there are still opportunities to further enhance the magnitude and multifunctionalities of ecosystem services that would be obtained in the optimal land management scenario. All watersheds analysed in this study showed climate smartness at the landscape level, with some level of difference among them. Gudoberet and Aba Gerima watersheds showed more climate smartness than the Anjeni and Debre Mewi. The study shows that investigating the multiple functions of more than five ecosystem services can be designated as multifunctional landscapes.